Cubic tungsten carbides: synthesis and lattice constant control; Известия вузов. Физика; Т. 58, № 9-3 - Pak A. Ya. Aleksandr Yakovlevich; Sivkov A. A. Aleksandr Anatolyevich; Shatrova K. N. Kseniya Nikolaevna; Shanenkov I. I. Ivan Igorevich (2015, 2015)
Заглавие с экрана